Preparation of starch-based scaffolds for tissue engineering by supercritical immersion precipitation - Duarte, Ana Rita C. (2009)
The aim of this study was to evaluate the possibility of preparing starch-based porous matrixes using supercritical fluid technology. Supercritical immersion precipitation technique was used to prepare scaffolds of a polymeric blend of starch and poly(l-lactic acid) for tissue engineering purposes.Immersion precipitation experiments were carried out at different operational conditions and highly porous and interconnected scaffolds were obtained. Two organic solvents, dichloromethane and chloroform were tested, and from the results obtained chloroform was the more favourable for the process. The effect of polymer solution concentration (5 up to 20 wt%), temperature (35 up to 55 ◦C) and pressure (100 up to 200 bar) in the SPLA (50:50 wt%) membrane morphology, porosity and interconnectivity was evaluated. All the conditions tested were in the region of total miscibility between the organic solvent and carbon dioxide. Additionally, a blend with a different starch-poly(l-lactic acid) ratio (30:70 wt%) was tested. Bicontinuous structures were formed indicating that the L–L demixing process that governs the phase inversion is the spinodal decomposition.